On the tenors of the symphony of nature-culture - Dahlig, Piotr (Interdisciplinary Studies in Musicology, 2018)
The question of nature-culture and music is approached in the text from several perspectives as points of gravity and profiles, as the ‘tenors’ of considerations of the nature-culture relationship within the context of musical behaviours: 1) the biological tenor - culture as the simulation or imitation of nature (the dominant feature of the art of the Palaeolithic and the rituals of the Neolithic; derivatives in agrarian cultures); in this context, all musical behaviours, the kinetic, verbal, social and symbolic were centred around obtaining and celebrating crops - the results of purposeful activity, patient waiting and the benevolence of supernatural powers. The joy from a powerful hope in the survival of a community through abundant harvests seems to have been the source of the synergy (mutual stimulation) of all the components of socio-musical events, collective rituals and free individual expression. 2) the social tenor, where verbal-dance-musical behaviours (generally speaking - amusement) serve to ‘hew off and distinguish an individual within a group (‘nature’). Thus the nature-culture relationship is translated or reflected in the interplay between the collective and the individual. The dance itself is a play between the (‘natural’) group action and the (‘cultural’) individualised performance. The oscillation between the action of a group and the display of an individual also occur in whirling dances of couples interspersed with individual sung ditties. The social tenor, the transition from collective nature to a culture that is also individual, also concerns the practising of song repertoire, and it is an important factor in understanding cultural change. 3) the conscious-psychological tenor, in which music and musical behaviour are conscious manifestations of culture within historical processes, without necessary references to nature. The fundamental question in this aspect of discussion is the relative extent to which culture is given or created. There is no doubt that nature is given to man, whilst culture needs time. Reflection on the link between music and the social environment leads to the conclusion that nature tightens, while culture loosens, music’s bond with the situational-social context that is strictly ascribed to it. 4) the structural tenor of the musical work/behaviour, which highlights the microworld of nature-culture, particularly the oscillation of openness/change and closedness/ constancy of musical works or behaviours. The nature-culture model can be referred to the logic of development or stylistic change in musical output itself. Following that quartet of tenors, it is worth posing the question as to whether there exists a fifth, linking all the previous four, a ‘cosmic’, theological tenor in the symphony of nature-culture; in other words, whether there exists a ‘school’ of tenors.